2022
DOI: 10.1101/2022.07.07.499165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corticostriatal Beta Power Changes Associated with Cognitive Function in Parkinson’s Disease

Abstract: Cognitive impairment (CI) is the most frequent nonmotor symptom in Parkinsons Disease (PD) and is associated with deficits in executive functions such as working memory. Previous studies have demonstrated that caudate beta power underlies learning and working memory. Decreased dopamine in motor cortico-striato-thalamo-cortical (CSTC) circuits results in increased beta power and PD motor symptoms. Analogous changes in cognitive CSTC circuits, including the caudate and dorsolateral prefrontal cortex (DLPFC), may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…Our results motivate to conceptualise the capacity to generate beta oscillations as a feature that arises from a large-scale global brain network that is modulated by dopamine. However, we do not see this concept as contradictory to previous reports of functional correlates of beta activity in the domains of motor control, cognition, memory and emotion 3,6,7,22 . Instead, we believe that the overlap in oscillatory activity across these domains can be conceptualised through a circuit definition of beta activity and its relationship to dopamine signalling.…”
Section: Brain Functions Associated With Beta Oscillations Share Brai...contrasting
confidence: 99%
See 2 more Smart Citations
“…Our results motivate to conceptualise the capacity to generate beta oscillations as a feature that arises from a large-scale global brain network that is modulated by dopamine. However, we do not see this concept as contradictory to previous reports of functional correlates of beta activity in the domains of motor control, cognition, memory and emotion 3,6,7,22 . Instead, we believe that the overlap in oscillatory activity across these domains can be conceptualised through a circuit definition of beta activity and its relationship to dopamine signalling.…”
Section: Brain Functions Associated With Beta Oscillations Share Brai...contrasting
confidence: 99%
“…Oscillatory neural activity is proposed to orchestrate brain function, by providing multilateral rhythmic synchronisation of neural excitability and action potential firing 1 . One prominent example in the human brain is the beta rhythm (13 – 35 Hz), which has traditionally been described as a phenomenon of the motor domain, primarily localised to motor cortex and important for the pathophysiology of movement disorders, such as Parkinson’s disease (PD) 2,3 . In PD, beta activity, especially in deeper brain structures, such as the basal ganglia, has been associated with the loss of innervation with dopamine 4 , a neurotransmitter critically involved in synaptic plasticity and reinforcement learning at cortico-striatal synapses 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that there is a close relationship between working memory and neural oscillations (such as theta frequency band/gamma frequency band) in the cortex/hippocampus/subthalamic nucleus and other brain areas [6], [7]. For example, in Parkinson's patients, the spectral power of beta oscillations in the prefrontal cortex and caudate nucleus decreases during working memory encoding, while the spectral power of these structures increases during feedback [8], [9]. There are also studies proving that changes in neural oscillations in the alpha and theta frequency bands of the parietal lobe are related to sequential working memory in Parkinson's disease.…”
Section: Abstract-cognitive Impairment Is One Of the Most Common Non-...mentioning
confidence: 99%
“…Previous work has shown that beta band neural oscillations in the caudate and DLPFC increase during reward-related feedback of cognitive tasks in human subjects. [37][38][39] However, whether these corticostriatal reward-related neural oscillations are altered in depression is not known. Moreover, how reward and emotional processing may interact is not well understood.…”
Section: Introductionmentioning
confidence: 99%